High frequency of cerebrospinal fluid autoantibodies in patients with seizures or epilepsies of unknown etiology - Schulz, Paulina; Lütt, Alva; Stöcker, Winfried; Teegen, Bianca; Holtkamp, Martin; Prüss, Harald (Frontiers in Neurology, 2023)
Introduction The increasing identification of specific autoantibodies against brain structures allows further refinement of the group of autoimmune-associated epilepsies and affects diagnostic and therapeutic algorithms. The early etiological allocation of a first seizure is particularly challenging, and the contribution of cerebrospinal fluid (CSF) analysis is not fully understood. Methods In this retrospective study with a mean of 7.8 years follow-up involving 39 well-characterized patients with the initial diagnosis of new-onset seizure or epilepsy of unknown etiology and 24 controls, we determined the frequency of autoantibodies to brain proteins in CSF/serum pairs using cell-based assays and unbiased immunofluorescence staining of unfixed murine brain sections. Results Autoantibodies were detected in the CSF of 30.8% of patients. Underlying antigens involved glial fibrillary acidic protein (GFAP) and N-methyl-D-aspartate (NMDA) receptors, but also a range of yet undetermined epitopes on neurons, glial and vascular cells. While antibody-positive patients had higher frequencies of cancer, they did not differ from antibody-negative patients with respect to seizure type, electroencephalography (EEG) and cranial magnetic resonance imaging (cMRI) findings, neuropsychiatric comorbidities or pre-existing autoimmune diseases. In 5.1% of patients with seizures or epilepsy of initially presumed unknown etiology, mostly CSF findings resulted in etiological reallocation as autoimmune-associated epilepy. Discussion These findings strengthen the potential role for routine CSF analysis. Further studies are needed to understand the autoantibody contribution to etiologically unclear epilepsies, including determining the antigenic targets of underlying autoantibodies.